Study on R&D result subsidy strategies for PEV enterprises based on heterogeneous consumer technology thresholds and preferences under anxiety issues - Ye Wang (PLoS ONE, 2025)
Many governments worldwide hoped to stimulate Pure Electric Vehicle(PEV) enterprises’ R&D and sales through R&D result subsidy policies, but the anxiety issues significantly reduced PEV sales and weakened the policy effectiveness. To achieve better incentive effects, considering the impact of anxiety issues on subsidy strategies is necessary. As anxiety problems stem from typical behavior characteristics of PEV consumers——consumer technology thresholds, reasonable study should understand them and quantify their impact from the perspective of consumer technology thresholds. Therefore, it constructs a sequential game model among the government, the PEV company, and consumers with two dimensions of heterogeneous behavior characteristics——technology thresholds and preferences. It also determines the optimal R&D result subsidy strategies and analyzes the impact of the technology thresholds and preferences on them. It shows that the government should provide subsidies except for PEV enterprises with R&D efficiency in the higher range, and its optimal strategies must consider consumer technology threshold and preference conditions. The lower the technology thresholds of PEV consumers, the lower the optimal subsidy ratio until the technology level of the enterprise is already high enough, and there is no need for subsidies. Higher consumer technology preferences of PEV consumers will achieve the same effect. The numerical simulation shows that compared to other models, the model considering PEV consumer technology thresholds can optimize the subsidy ratio and achieve better incentive effects.